Chromosome studies of Brazilian vespertilionids Lasiurus cinereus and Lasiurus ega (Mammalia, Chiroptera) - Marchesin, Sandra Regina De Carvalho [UNESP] (2004)
Cytogenetical studies based on conventional coloration by Giemsa, C-banding and Ag-NOR were performed on 2 species of bats from the vespertilionid family: Lasiurus cinereus (Beauvois, 1796) and Lasiurus ega (Gervais, 1856). The 2n was 28 and FN was 48 in both species. The constitutive heterochromatin is located in centromeric regions in the two species and in the short arm of the subtelocentric X chromosome in L. ega. NORs were observed in the secondary constriction of the smaller autosome in both species.